Reflections on The Possibility of Using Statistical Analysis Science and Innovation in The Republic of Moldova - Turcan (Susu) Aurelia (International Business and Accounting Research Journal, 2017)
The evaluation and comparability of statistics indicators of the   science and innovation  on international background reflect country competitiveness and it position regarding field of science, innovation and distribution of new technologies. Better comprehensions of the factors that contribute at the success in these fields are helped by using proper indicators like instruments of identification of the best practice. But the system of indicators is developed only for the ”science”. The ”innovation” in Moldova is not covered by statistical work and can only be assessed indirectly.